(untitled) (MIST International Journal of Science and Technology, 2025)
Molten salt tanks are crucial in photovoltaic power plants, serving as the core of new energy-storage systems. Although suitable for small-area domestic heating, they are complex in structure and prone to significant heat loss. To address these issues, this study proposes a novel single-tank molten salt system that combines monitoring, preheating, heat exchange, and storage functionalities. By incorporating a U-tube heat exchanger within the molten salt accumulator, the system achieves cost-effective heat storage and release. The effectiveness of the heat extraction method used with the U-tube profoundly affects the overall system performance. Through numerical simulations, this study examines the impact of different heat extraction techniques on the performance of the single-tank heat storage system, focusing on changes in the flow field within the molten salt during heat release. By modifying operational conditions, improvements in outlet temperature, heat release power, and heat utilization efficiency of the U-tube heat exchanger are demonstrated. This study explores the heat release process in a single tank of molten salt using 3D unsteady Computational Fluid Dynamics (CFD) simulations. Operation behaviour estimate results show that varied initial temperatures of the molten salt have distinct impacts on the thermal behavior of the system. Higher initial temperatures lead to a smaller temperature differential between the highest and lowest points in the tank during the same exothermic periods. And under conditions of constant inlet velocity, the exothermic power decreases as the duration of heat release increases. In scenarios with a constant inlet mass flow rate, the time required to reach the limit of exothermic power decreases as the mass flow rate increases. Throughout the exothermic process, the average heat flow density gradually declines. This decline is particularly notable in the first 10 minutes of the exothermic activity. As the process progresses, the average temperature through the heat transfer oil within the heat exchanger increases, which reduces the temperature differential between the hot and cold fluids, further decreasing the average heat flow density. MIJST, Vol. 12, December 2024 : 13-21 DOI: https://doi.org/10.47981/j.mijst.12(02)2024.470(13-21)